2012
DOI: 10.1093/nar/gks668
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensionally designed protein-responsive RNA devices for cell signaling regulation

Abstract: The three-dimensional (3D) structures of many biomacromolecules have been solved to reveal the functions of these molecules. However, these 3D structures have rarely been applied to constructing efficient molecular devices that function in living cells. Here, we demonstrate a 3D structure-based molecular design principle for constructing short hairpin RNA (shRNA)-mediated genetic information converters; these converters respond to specific proteins and trigger the desired gene expression by modulating the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Here, we present a robust and reversible RNA-based switching element that allows efficient control of miRNA processing. Previous work documented ‘one-way’ switching of small non-coding RNA biogenesis to switch off processing through the addition of the respective ligands to aptamer-coupled systems ( 25 , 26 , 28 , 29 , 53 ). However, for short-term interference applications, the operating system must be fully reversible to allow a recovery to the original expression level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present a robust and reversible RNA-based switching element that allows efficient control of miRNA processing. Previous work documented ‘one-way’ switching of small non-coding RNA biogenesis to switch off processing through the addition of the respective ligands to aptamer-coupled systems ( 25 , 26 , 28 , 29 , 53 ). However, for short-term interference applications, the operating system must be fully reversible to allow a recovery to the original expression level.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparable approach, various aptamers together with competing strands were integrated into shRNA loop structures affecting the processing of the respective shRNAs by ligand-dependent switching between two structural conformations ( 26 ). Furthermore, protein-binding motifs for the human U1A protein and L7Ae, or the p50-binding aptamer positioned in the shRNA loop region have been shown to regulate shRNA processing by Dicer ( 27 , 28 ). In another design, small molecule or protein-binding aptamers were integrated into the basal segment of a synthetic pri-miRNA bearing an siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated control of living cells demands synthetic gene circuits that are capable of sensing multiple endogenous molecular signals. RNA interference provides a versatile interface that allows synthetic gene circuits to modularly sense and integrate endogenous molecular inputs in mammalian cells 18 , 44 - 48 . In this work, we demonstrated that endogenous microRNAs can be used to control the state of TALER sensory switches and that the sensitivity of TALER switches to shRNAs is tunable by adjusting the ratio of the two primary components.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a novel design of aptamer-siRNA fusions enabled siRNA-processing control in mammalian cells (Fig. 2C) (Kashida et al 2012). Proteinbinding RNA aptamers (e.g., U1A protein-U1A RNA motif ) have been engineered into siRNA precursors that can replace RNA stem loops that are essential for siRNA processing.…”
Section: Posttranscriptional Gene Switchesmentioning
confidence: 97%